2022
DOI: 10.3389/fgwh.2022.817817
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Interventions for Preterm Infants in LMICs: A Prospective Study From Cape Town, South Africa

Abstract: BackgroundPreterm birth is a global public health issue and complications of preterm birth result in the death of approximately 1 million infants each year, 99% of which are in low-and-middle income countries (LMIC). Although respiratory interventions such as continuous positive airway pressure (CPAP) and surfactant have been shown to improve the outcomes of preterm infants with respiratory distress, they are not readily available in low-resourced areas. The aim of this study was to report the respiratory supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
8
1
Order By: Relevance
“…When it comes to antenatal steroids, the coverage in this study had improved slightly (from 39.1 to 48%) compared to 2013 (12). However, this remains poor compared to other South African studies (15,16,22). Despite this improvement the goal should be even higher since antenatal steroids have an effect on RDS (hence the amount of respiratory support required for patients), as well as the rates of NEC and IVH (23).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…When it comes to antenatal steroids, the coverage in this study had improved slightly (from 39.1 to 48%) compared to 2013 (12). However, this remains poor compared to other South African studies (15,16,22). Despite this improvement the goal should be even higher since antenatal steroids have an effect on RDS (hence the amount of respiratory support required for patients), as well as the rates of NEC and IVH (23).…”
Section: Discussioncontrasting
confidence: 61%
“…Despite this improvement the goal should be even higher since antenatal steroids have an effect on RDS (hence the amount of respiratory support required for patients), as well as the rates of NEC and IVH (23). Lategan et al found that exposure to any antenatal steroids was associated with a nearly three-quarter reduction in mortality in their cohort of preterm infants ≤1,800 (15). Concerted efforts need to be made to further improve the coverage of antenatal steroids.…”
Section: Discussionmentioning
confidence: 99%
“… 84 They are therefore currently unavailable in many resource-limited settings, which is estimated to have a significant impact on neonatal mortality in these populations. 85 …”
Section: Supportive Carementioning
confidence: 99%
“…The main causes of early death during the neonatal age are serious complications associated with prematurity [1]. In almost every African country, mortality is higher in newborns under 32 weeks [1,4,5]. Democratic Republic of Congo (D.R.C.)…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the recommendations of the World Health Organization (WHO) [1], interventions such as antenatal corticosteroid therapy (ACS), the use of CPAP and surfactant are among the most effective means for improving the management of premature babies [1,5,9].…”
Section: Introductionmentioning
confidence: 99%